Analog electronics applications : fundamentals of design and analysis - Fernandez-Canque, Hernando Lautaro (CRC Press, 2017)
This comprehensive text discusses the fundamentals of analog electronics applications, design, and analysis. Unlike the physics approach in other analog electronics books, this text focuses on an engineering approach, from the main components of an analog circuit to general analog networks. Concentrating on development of standard formulae for conventional analog systems, the book is filled with practical examples and detailed explanations of procedures to analyze analog circuits. The book covers amplifiers, filters, and op-amps as well as general applications of analog design.
Keywords: Analog electronic systems.; Electronic circuits.; Electronics.; elektronické knihy; electronic books